Synergy of image analysis for animal and human neuroimaging supports translational research on drug abuse - Gerig, Guido; Oguz, Ipek; Gouttard, Sylvain; Lee, Joohwi; An, Hongyu; Lin, Weili; McMurray, Matthew; Grewen, Karen; Johns, Josephine; Styner, Martin A. (Frontiers in Psychiatry, 2011)
The use of structural magnetic resonance imaging (sMRI) and diffusion tensor imaging (DTI) in animals models of neuropathology is of increasing interest to the neuroscience community. In this work, we present our approach to create optimal translational studies that include both animal and human neuroimaging data within the frameworks of a study of postnatal neuro-development in intra-uterine cocaine exposure. We propose the use of non-invasive neuroimaging to study developmental brain structural and white matter pathway abnormalities via sMRI and DTI, as advanced MR imaging technology is readily available and automated image analysis methodology have recently been transferred from the human to animal imaging setting. For this purpose, we developed a synergistic, parallel approach to imaging and image analysis for the human and the rodent branch of our study. We propose an equivalent design in both the selection of the developmental assessment stage and the neuroimaging setup. This approach brings significant advantages to study neurobiological features of early brain development that are common to animals and humans but also preserve analysis capabilities only possible in animal research. This paper presents the main framework and individual methods for the proposed cross-species study design, as well as preliminary DTI cross-species comparative results in the intra-uterine cocaine exposure study.